Accelerating anaemia reduction: a comprehensive framework for action - WHO (WHO, 2023)
A key theme throughout this document is that progress in reducing anaemia depends on the meaningful participation of stakeholders at all levels, including national and local governments, educational institutions, civil society organizations, food producers, and local and international organizations.
Keywords: Strategy, Policy, Non-communicable diseases